Integration of Rural Elements into Urban Areas - A Tangible Nostalgia and Sustainability Aid in Developing Countries - Femi Emmanuel Arenibafo (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
In developing countries, people are inevitably moving in a large scale from rural settlements into urban areas for a supposed better opportunity and improved financial situation. This internal migration unarguably mounts pressure and imposes threats on the urban centers, forcing an uncontrolled expansion. Consequently, there’s a severe impact on natural surfaces, ecosystems, the climate and a below standard quality of life for urban dwellers. Withal, projection shows that by 2050, 70% of the world’s population will be living in urban centers. This seems unstoppable but can be manageable. Hence, this paper seeks to qualitatively emphasize the problems and threats of urban sprawl, to create bases for discussion and polemics, as well as advocate the need and long term benefits of integrating rural elements into urban regions as regards spatial planning, landscape/land use, architecture, and aesthetics. In turn, gives tangible aid to the nostalgia and sense of place feeling of green souls who inevitably move from rural into the urban concrete jungle, equally creating a paradigm for the achievable UN sustainable development goals 3 and 11 in particular and other relatable goals 1,2,12 and 15 in developing countries.